2010
DOI: 10.1051/0004-6361/201014233
|View full text |Cite
|
Sign up to set email alerts
|

VLBI study of maser kinematics in high-mass star-forming regions

Abstract: Aims. To study the high-mass star-forming process, we started a large project to unveil the gas kinematics close to young stellar objects (YSOs) through the Very Long Baseline Interferometry (VLBI) of maser associations. By comparing the high spatial resolution maser data that traces the inner kinematics of the (proto)stellar cocoon with interferometric thermal data that traces the large-scale environment of the hot molecular core (HMC) harboring the (proto)stars, we can investigate the nature and identify the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 78 publications
(78 citation statements)
references
References 49 publications
3
74
1
Order By: Relevance
“…This timescale and the nature of variability found here (eruptive, dipper, LPV) are very similar to the variations of the 6.7 GHz class II methanol maser emission in high-mass star-forming regions, both in its nature (Goedhart et al 2004) and in the timescales (Goedhart et al 2014). The class II methanol masers are thought to be pumped by infrared radiation (Cragg et al 2005) and found to originate in accretion disks in highmass star-forming regions (Sanna et al 2010;Sugiyama et al 2014). The similarity in the variability found in the methanol maser emission (MME) and the IR variability may therefore represent the frequency of the infrared luminosity variations of the warm disk from accretion events, which is also responsible for pumping the class II MME (Cragg et al 2005).…”
Section: Discussionsupporting
confidence: 83%
“…This timescale and the nature of variability found here (eruptive, dipper, LPV) are very similar to the variations of the 6.7 GHz class II methanol maser emission in high-mass star-forming regions, both in its nature (Goedhart et al 2004) and in the timescales (Goedhart et al 2014). The class II methanol masers are thought to be pumped by infrared radiation (Cragg et al 2005) and found to originate in accretion disks in highmass star-forming regions (Sanna et al 2010;Sugiyama et al 2014). The similarity in the variability found in the methanol maser emission (MME) and the IR variability may therefore represent the frequency of the infrared luminosity variations of the warm disk from accretion events, which is also responsible for pumping the class II MME (Cragg et al 2005).…”
Section: Discussionsupporting
confidence: 83%
“…To obtain the averaged positions for a maser spot (procedure 3), we performed parallax fits on all the individual spots and removed their position offsets and proper motions, after which we averaged the positions of each epoch. The last approach has the advantage of reducing the random errors, introduced by small variations in the internal spot distribution for a maser feature (e.g., Sanna et al 2010), while leaving the systematic errors unaffected.…”
Section: Parallax Fittingmentioning
confidence: 99%
“…This evidence favors the interpretation of the radio continuum as an ionized jet and suggests that water masers may originate in shocks produced by the interaction of the jet with the surrounding molecular environment. For optically thin emission, F d 2 = 10 3.5 (Ω/4π)Ṗ j (Sanna et al 2010), where F is the measured continuum flux in mJy,Ṗ j is the jet momentum rate in M yr −1 km s −1 , Ω is the jet solid angle in sr, and d is the source distance in kpc. Using a flux density of 0.24 mJy (0.17 mJy) measured at 8.4 GHz for the NW (SE) component and a distance of 1.8 kpc, we deriveṖ j = 2.5(1.7) × 10 −4 (Ω/4π) −1 M yr −1 km s −1 .…”
Section: Collimated Outflow From Mm-1mentioning
confidence: 99%